2009
DOI: 10.1007/s00520-009-0714-3
|View full text |Cite
|
Sign up to set email alerts
|

Personality predicts perceived availability of social support and satisfaction with social support in women with early stage breast cancer

Abstract: Besides factors, like fatigue and having a job, personality factors substantially influence the way women with early stage BC perceive social support. Knowledge about these underlying mechanisms of social support is useful for the development of tailor-made interventions. Professionals should be aware of the importance of social support. They should check whether patients have sufficient significant others in their social environment and be sensitive to potential discrepancies patients might experience between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 46 publications
0
22
1
1
Order By: Relevance
“…Professionals should be aware that personal, clinical and social factors could substantially influence the way patients perceive social support and be sensitive to discrepancies patients might experience between availability and adequacy of social support. 18 We add here a comment on the direction of outcomes observed in this study. The negative outcome as measured by the instruments in a substantial proportion of patients was not reflected in gross outcomes like rehospitalisation or discontinuity from the rehabilitation program.…”
Section: Discussionmentioning
confidence: 89%
“…Professionals should be aware that personal, clinical and social factors could substantially influence the way patients perceive social support and be sensitive to discrepancies patients might experience between availability and adequacy of social support. 18 We add here a comment on the direction of outcomes observed in this study. The negative outcome as measured by the instruments in a substantial proportion of patients was not reflected in gross outcomes like rehospitalisation or discontinuity from the rehabilitation program.…”
Section: Discussionmentioning
confidence: 89%
“…Findings from prior research on perceived social support in breast cancer patients are mixed. Prior work has suggested that many women report having increased support around the time of cancer diagnosis, but that this support often decreases over time after treatment (Den Oudsten et al, 2010; Courtens et al, 1996; Bloom and Kessler, 1994), a decrease that may be associated with negative psychosocial outcomes (Thompson et al, 2013). Not all studies have found a decline in social support after diagnosis, however.…”
mentioning
confidence: 99%
“…Six of them originated in the United States [7]- [10] [14] [15]; one paper was published in Canada [12], another one in England [13], one in Holland [11], and one paper was published in Israel [16].…”
Section: Resultsmentioning
confidence: 99%
“…Some report that a lack of balance is perceived when support requested is not provided or when the support provided was not the support sought. One should take into account that perception of social support may be influenced by personality factors along with one's psychological state [11].…”
Section: Discussionmentioning
confidence: 99%